Deletion of α4 Integrins from Adult Hematopoietic Cells Reveals Roles in Homeostasis, Regeneration, and Homing - Scott, Linda M. (American Society for Microbiology, 2003)
We have explored the functional implications of inducible α4 integrin deletion during adult hematopoiesis by generating a conditional-knockout mouse model, and we show that α4 integrin-deficient hematopoietic progenitor cells accumulate in the peripheral blood soon after interferon-induced gene deletion. Although their numbers gradually stabilize at a lower level, progenitor cell influx into the circulation continues at above-normal levels for more than 50 weeks. Concomitantly, a progressive accumulation of progenitors occurs within the spleen. In addition, the regeneration of erythroid and myeloid progenitor cells is delayed during stress hematopoiesis induced by phenylhydrazine or by 5-fluorouracil, suggesting impairment in early progenitor expansion in the absence of α4 integrin. Moreover, in transplantation studies, homing of α4(−/−) cells to the bone marrow, but not to the spleen, is selectively impaired, and short-term engraftment is critically delayed in the early weeks after transplantation. Thus, conditional deletion of α4 integrin in adult mice is accompanied by a novel hematopoietic phenotype during both homeostasis and recovery from stress, a phenotype that is distinct from the ones previously described in α4 integrin-null chimeras and β1 integrin-conditional knockouts.